Role of Farmers in Supply Chain Management of Horticultural Products - M. Bhavya Manjari; M. Suryamani (Journal of Agricultural Extension Management, 2014)
The horticultural crop in the country presently covers 13.6 million hectares of land i.e., 7 per cent of the gross cropped area and contributes 18-20 per cent of the gross value of India’s agricultural output. However, the post harvest loss in fruits and vegetables is estimated to be around 35-40 per cent of the production. This necessitates effective and efficient Supply Chain Management (SCM). Various initiatives are attempting to strengthen the supply chain and provide benefits to the farmers. This study examines the role of farmers in supply chain management of horticultural products. The study examined the farmer’s role in planning for production of horticultural crops and SCM, procurement of material, credit arrangement, production management, post harvest management of vegetables and fruits, processing, information management and marketing. Results reveal that majority of the farmers had medium level of participation in planning and procurement of material. Majority of the farmers had high participation in production management and no participation in credit arrangement, post-harvest management, processing and marketing through SCM models.